Current Technological Trends in Transdermal Biosensing. Issue 9 (28th June 2022) - Zhang, Yuyue; Yang, Cheng; Shi, Haibin; Xu, Chenjie
Abstract : Transdermal biosensing focuses on the qualitative and quantitative collection and detection of biomarkers on and in the skin layers. In comparison to the blood‐based diagnosis, transdermal sensing technologies provide pain‐free, convenient, patient‐friendly, and infection‐avoiding methods to collect biosignals from transdermal samples such as interstitial fluid (ISF) and sweat. This article summarizes the latest trends in transdermal biosensing including the technologies and their application blueprints. Specifically, the current transdermal biosensing technologies including microneedles, microfluidics, and reverse iontophoresis are introduced first. Subsequently, their roles in daily health status monitoring, disease diagnosis and therapy monitoring are discussed in detail. Finally, an overview of the future blueprints and application prospects of transdermal biosensing is provided. Abstract : Transdermal biosensing focuses on the qualitative and quantitative collection and detection of biomarkers on and in the skin layers. It collects biosignals from transdermal samples (skin interstitial fluid or sweat). This article summarizes the latest trends in this field including the technologies and their application blueprints.